2018
DOI: 10.1073/pnas.1800996115
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 2 inhibition preferentially promotes NO/guanylyl cyclase/cGMP signaling to reverse the development of heart failure

Abstract: SignificanceThe morbidity and mortality associated with heart failure (HF) are unacceptably high. Cyclic guanosine-3′,5′-monophosphate (cGMP) plays a key role in preserving cardiac structure and function, and therapeutically targeting cGMP in HF has shown promise in experimental models and patients. Phosphodiesterases (PDEs) metabolize and curtail the actions of cGMP (and cAMP), and increased PDE activity is thought to contribute to HF pathogenesis. Herein, we show that inhibition of one specific isoform, PDE2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 79 publications
(134 reference statements)
2
28
0
Order By: Relevance
“…Likewise, PDE2i curtails the development of LVH, compromised contractility and cardiac fibrosis in pressure overload-induced HF. Rather than amplifying cAMP signalling, inhibition of PDE2 augments cGMP signalling, which is dependent upon endogenous NO activity and stimulation of GC-1 (rather than NP-activated GC-A) [87]. This supports previous suggestions that increases in cGMP produced by PDE2i functions akin to cAMP to curtail fibroblast to myofibroblast conversion and restrain fibrosis [91].…”
Section: Heart Failure Pathophysiologysupporting
confidence: 86%
See 2 more Smart Citations
“…Likewise, PDE2i curtails the development of LVH, compromised contractility and cardiac fibrosis in pressure overload-induced HF. Rather than amplifying cAMP signalling, inhibition of PDE2 augments cGMP signalling, which is dependent upon endogenous NO activity and stimulation of GC-1 (rather than NP-activated GC-A) [87]. This supports previous suggestions that increases in cGMP produced by PDE2i functions akin to cAMP to curtail fibroblast to myofibroblast conversion and restrain fibrosis [91].…”
Section: Heart Failure Pathophysiologysupporting
confidence: 86%
“…Although β 3 -AR expression within the myocardium is contentious [86], this corresponds well with the different actions attributed to NO/cGMP and NP/ cGMP on contractility. That is, whilst NO acts, primarily, as a negative inotrope, ANP either reduces or has no effect on inotropy [87,88]. PDE2 also promotes cardiomyocyte apoptosis [89] and is highly expressed in cardiac fibroblasts where it regulates myofibroblast formation and fibrosis by counteracting the increase in cAMP in response to ISO and β-AR stimulation [90,91].…”
Section: Cardiac Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Whether the permeability of gap junction‐dependent diffusion of cGMP from the fibroblasts to the cardiac myocytes is also under control of hormones or intracellular signalling events has to be addressed in forthcoming studies. In a very recent publication, a beneficial effect of PDE2 inhibition in heart failure was shown to depend on cGMP formed by NO–GC, underlining the important function of the NO receptor in the heart (Baliga et al, ). Yet first and foremost, the presence of cGMP in cardiac myocytes as a result of NO–GC stimulation in fibroblasts has to be confirmed in whole heart preparations and then the way is paved for the identification of NO/cGMP effects in the working heart.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) is a fundamental signaling molecule involved in several physiological processes including host defense, and the regulation of vascular tone as well as a potent cytotoxic effector involved in human diseases pathogenesis (62), Griffin et al showed that decreased ATP2A3 expression induces unfolded protein response (UPR) in Jurkat cells (65) and our sequencing results also observed that down-regulation of ATP2A3 resulted in induction of unfolded protein response in these cells. Recently, researchers showed decreased PDE2A expression leads to increased accumulation of cAMP and myocardial contractility after beta-adrenogenic receptor stimulation (66, 67). Sequencing results also showed down-regulation of PDE2A level.…”
Section: Discussionmentioning
confidence: 99%